An electrochemical sensing platform for sensitive detection DNA methylation using Fe3O4/TMC/Au nanocomposite and poly(l-arginine)/reduced graphene oxide modified screen-printed carbon electrode - Syedmoradi, Leila; Hajghassem, Hassan; Tavoosidana, Gholamreza; Rezayat, Seyed Mahdi; Faridi-Majidi, Reza; Omidfar, Kobra (Journal of Contemporary Medical Sciences, 2018)
Objectives: In this study, a simple electrochemical nano-genosensor has been developed for the rapid and sensitive detection of methylated SEPT9 DNA as a useful biomarker for early colorectal cancer detection or screening. Methods: The process consists of three main steps: (i) the surface modification of screen-printed carbon electrode (SPCEs) with a poly(l-Arg)/RGO composite film followed by immobilizing anti-5-methylcytosine antibody (ii) preparation of probe-modified Fe3O4/TMC/Au nanocomposites for the hybridization with complementary DNA sequences, (iii) capturing methylated DNA target by antibody-modified SPCEs and subsequent electrochemical detection through redox peak currents of gold nanoparticles which generated a concentration-dependent response. Results: The surface modification of the electrode and hybridization with the methylated target were confirmed by cyclic voltammetry (CV) method and differential pulse voltammetry (DPV) was employ for quantitative evaluation of methylated target DNA. Conclusion: The assay showed a wide linear range from 0.01 pM to 1000 pM with a low detection limit of 0.01pM.